Dinámica de perturbación-recuperación de las zonas forestales en el Parque Nacional Nevado de Toluca - Franco Maass, Sergio; Regil García, Héctor Hugo; Ordóñez Díaz, José Antonio Benjamín (Instituto de Ecología, A.C., 2016)
Despite the severe problems of deforestation that suffer the forests in México, there are only a few detailed studies to identify, in a very precise manner, the dynamics of disturbance or recovery of such ecosystems. In the present work, a detailed methodology to analyze the land cover change in the Nevado de Toluca National Park is presented. With the aid of Geografical Information Systems and the production of two land cover maps of the national park for two different years (1972 and 2000), it was possible to obtain a map of changes. The transition observed in this map was then re-classified with a loss or gain criteria and, with this, it was possible to obtain a final map of forest disturbance-recovery. The national park presented a deforestation rate of 8,4%, with a land cover change of more than 2 000 hectares along the period.